Acceptance Analysis Of Web-Based Learning Media In Indramayu Regency Based On The UTAUT2 Model - Ileena Ramadhanti; Yunus Abidin (STKIP Singkawang, 2024)
The current education system has adopted a 21st-century approach, emphasizing learning to know, learning to do, learning to be, and learning to live together. This shift has moved from a teacher-centered to a student-centered learning approach. 21st-century education demands the development of learning skills, innovation, information literacy, and digital literacy. The aim is to assess the extent to which variables such as Effort Expectancy (EE), Facilitating Conditions (FC), Hedonic Motivation (HM), ICT Usage Habits (IUH), Performance Expectancy (PE), Perceived Learning Opportunities (PLO), and Social Influences (SI) can influence Behavioral Intention (BI). Additionally, the study evaluates factors influencing the level of acceptance of web-based learning media usage among teachers in Indramayu Regency, using the UTAUT2 model.This research employs a qualitative descriptive method with a questionnaire as the instrument. The population comprises all teachers in Indonesia, with a sample of 100 elementary school teachers in Indramayu Regency. The findings indicate that variables EE, FC, HM, IUH, PE, PLO, and SI collectively have an 81.1% influence on Behavioral Intention (BI), while 18.9% is attributed to other unexplored factors. The hypothesis test results reveal that EE, FC, HM, IUH, PE, and SI do not significantly impact Behavioral Intention (BI). However, Perceived Learning Opportunities (PLO) has a significant influence on Behavioral Intention (BI).